إزالة الاشتباه في رواية الشيوخ والتلاميذ عند سفيان بن عيينة وسفيان الثوري في الرواية - بلميهوب, حفيظة; قرح, حسين (جامعة الوادي - University of Eloued, 2023)
ملخص: وهدف البحث: إبراز مكانة ومنزلة ابن عيينة والثوري الحديثية، وهما إماما هذا الشأن، وقد تشابها في الاسم، وإيضاح الاسم من المقصود في الإسناد إذا أبهم أحدهما للتفريق بينهما ومعرفة كل واحد منهما حديثه الذي رواه لئلا يدخل حديث في حديث. والنتائج المتوصل إليها: إزالة الاشتباه في الرّواة بين سفيان بن عيينة وسفيان الثّوريّ في الشّيوخ والتّلاميذ، فإذا صرّح الرّاوي عنهما زال الإشكال، وإذا لم يصرح فينظر إلى الرّاوي عنهما، وإن أصحاب الثّوريّ قدماء مثل ابن مَهْديّ وأبي نُعَيم والْفِرْيَابِيّ ووكَيع، وابن عُيْينة متأخر عنه قليلا. وأصحاب ابن عُيينة صغار؛ ففي بعضهم لم يدركوا سفيان الثّوريّ. وأنّ طبقات الرّواة مهم جدّا لمعرفة الرّاوي من روى عنه، وعن من روى. وإذا أطلق اسم الشّيخ مبهما ولم يعرف، فينظر من له اختصاص به واهتمام وملازمة. وابن عيينة إذا روى عن شيوخه الضّعفاء يذكرهم بأسمائهم، بينما الثّوريّ يكنيهم. Abstract : The aim of the research: to highlight the status and rank of Ibn Uyaynah and Al-Thawri Al-Hadith, the two imams in this descipline, and they are similar in the name, and to clarify the name from what is intended in the isnad if one of them is vague to differentiate between them and knowing each of them his hadith that he narrated so as not enter into a hadith. The outcomes reached: removing the narrators' suspicion between Sufyan bin Uyaynah and Sufyan Al-Thawri , their sheikhs and students. If they are mention there will not be any vague and if not, we should back to the narrators.The companions of Althawri are more ancient such as Ibn Mahdi, ABI Nouaim, Al Feriabi and Wakia. While Ibn Uyaynah companions are minors. In some of them did not catch Sufyan al-Thawri. Also, the layers of narrators is very important to know the narrator. If the name of the sheikh is ambiguous , we should consider who has specialization, interest and adherence to him. As well as, Ibn Uyaynah, if he narrates on the authority of his weak sheikhs, mentions them by their names, while al-Thawri calls them.
مقال
Keywords: الثوري ; ابن عيينة ; الاشتباه ; الرواية ; رواة; al-Thawri ; Ibn Uyaynah ; suspicion ; the novel ; narrator